Study on grid-tie inverter - Pan, Jinsong (2012)
Traditional generating systems such as (Coal) Turbines produce pollution that incurs high environmental costs. In addition, the large demand for energy in the world today will inevitably deplete the supply of non-renewable sources such as coal. Hence, world leaders are increasingly searching for alternatives to traditional generating systems. [1] Some of these alternatives include solar energy systems, wind energy systems and hydropower systems. Such systems make use of renewable sources and reduce little to no harm emissions hence making them more attractive alternatives.